Compact four‐port MIMO dielectric resonator antenna with pattern diversity. Issue 12 (26th July 2019) - Varshney, Gaurav; Gotra, Shailza; Chaturvedi, Saumya; Pandey, Vinay S.; Yaduvanshi, Rajveer S.
Abstract : A new compact four‐port multi‐input‐multi‐output (MIMO) dielectric resonator (DR) antenna is proposed with pattern diversity. The antenna contains four DR elements, the epsilon‐shaped and cylindrical. These four DR elements are placed together such that they resonate at the same frequency. The specific geometry of the DR elements allows to place them at separation which is much smaller than operating wavelength. Hence, the combination of the four DR elements acts as a single DR. This helps in maintaining the compactness of the antenna structure. The antenna operates with the hybrid of modes HE M 11 δ and T M 01 δ excited in epsilon‐shaped and cylindrical DR elements, respectively. The excitation of these orthogonal modes helps in obtaining the pattern diversity allowing the antenna for multi‐directional coverage. The antenna provides 15.73% overlapping 10 dB impedance bandwidth with the variation of gain within ranges 4–6 and 6–6.5 dBi at port 1/2 and port 3/4, respectively. In addition, the antenna provides the high radiation efficiency >93% at port 1/2 and 97% at port 3/4. Other parameters required for MIMO applications such as envelope correlation coefficient and diversity gain are within the acceptable limits.